DEVELOPMENT FRAMEWORK FOR MONITORING AND EVALUATION OF OPEN GOVERNMENT DATA QUALITY - Raca, Vigan; Velinov, Goran; Cico, Betim; Kon-Popovska, Margita (My University, 2021)
Open Government Data remains a worldwide challenge, in both developed and developing countries. There are various models for measuring the quality of Open Government Data but in our research paper, we have designed a framework for evaluating and Open Government Data quality. Target of evaluation are six Western Balkan countries, respectively Open Government Data portals with the possibility of extension to other countries. For assessment purposes, we have designed an application that uses combination of metrics based on two data quality dimensions, while in the background it will perform various calculations for showing results in a dashboard. The results will show the performance of each country as well as their quality progress in monthly basis.
Keywords: Open Data, Quality, Dataset, Government, Portal, Evaluation